Development of a multi-level/multi-modal intervention for health care transition preparation - Beth H. Garland; Mary Majumder; Constance M. Wiemann; Blanca Sanchez-Fournier; Jordyn Babla; Albert C. Hergenroeder (Health Care Transitions)
Aims: Health care transition (HCT) to adult care and young adult disease self-management is a multi-step process involving three major stakeholders – the adolescent, the caregiver, and the provider. Preparation gaps exist within each of these stakeholder groups. This paper presents the development of the Intervention to Promote Autonomy and Competence in Transition-aged Youth (IPACT), a multi-level (adolescent, caregiver, provider), multi-modal (interactive skill building sessions, educational materials, videos) intervention to address gaps in all three stakeholder groups simultaneously and help support achieving the three core elements of HCT planning. Methods: Eight processes were utilized to develop the IPACT intervention, including reliance on existing literature and materials, stakeholder feedback at multiple points during development, and regular support and guidance from service liaisons within each of four tertiary-care clinics targeted for this intervention within a large, urban children’s hospital. Conclusions: IPACT includes the conceptual schema, logic model, intervention curriculum components, and implementation timeline. IPACT could be used by programs to simultaneously address gaps in stakeholder HCT planning knowledge and skills.